2013
DOI: 10.1371/journal.pone.0079216
|View full text |Cite
|
Sign up to set email alerts
|

Difficulties with Pitch Discrimination Influences Pitch Memory Performance: Evidence from Congenital Amusia

Abstract: Music processing is influenced by pitch perception and memory. Additionally these features interact, with pitch memory performance decreasing as the perceived distance between two pitches decreases. This study examined whether or not the difficulty of pitch discrimination influences pitch retention by testing individuals with congenital amusia. Pitch discrimination difficulty was equated by determining an individual’s threshold with a two down one up staircase procedure and using this to create conditions wher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 32 publications
(35 citation statements)
references
References 49 publications
4
31
0
Order By: Relevance
“…3b shows the distribution of those effect sizes. The calculation of Cook's distances indicated that one effect size from Jiang, Lim, Wang, and Hamm (2013), with a value of r(26) ¼ À.57, exceeded Bollen and Jackman's (1985) criterion. Thus, this effect size was excluded from further analysis.…”
Section: Baseline Modelmentioning
confidence: 90%
“…3b shows the distribution of those effect sizes. The calculation of Cook's distances indicated that one effect size from Jiang, Lim, Wang, and Hamm (2013), with a value of r(26) ¼ À.57, exceeded Bollen and Jackman's (1985) criterion. Thus, this effect size was excluded from further analysis.…”
Section: Baseline Modelmentioning
confidence: 90%
“…Several studies note that short-term memory deficits in amusia persist even for stimuli that are above threshold (Albouy et al, 2013a, 2013b; Gosselin et al, 2009; Tillmann et al, 2009; Williamson et al, 2010). However, presenting the same stimuli for both amusics and controls means that pitch changes will be closer to amusics’ thresholds relative to controls (Jiang et al, 2013). Jiang et al note it is difficult to interpret findings from memory studies that have not controlled for pitch sensitivity because pitch sensitivity and memory are confounded.…”
Section: Experiments 2: Assessing the Role Of Memory Loadmentioning
confidence: 99%
“…These pitch distances are frequently below the pitch change and pitch direction detection thresholds of amusic individuals (Hyde & Peretz, 2004;Jiang, Lim, Wang, & Hamm, 2013;Peretz et al, 2002). As such, it has been speculated that low-level processing difficulties in amusia result in higher-level structure processing difficulties, such as syntax and tonality processing (Cousineau, McDermott, & Peretz, 2012;Stewart, 2011).…”
Section: --------------------------------------------------------mentioning
confidence: 99%
“…Pitch change detection and pitch direction discrimination thresholds were also measured for each participant using a two-alternative forced choice AXB procedure as reported in Jiang et al (2013). The amusic participants showed higher pitch thresholds and performed significantly worse than control participants on the MBEA (Table 1).…”
mentioning
confidence: 99%